EFFECTS OF PROCESS PARAMETERS AND OPTIMIZATION OF MECHANICAL AND METALLURGICAL BEHAVIOUR FOR DISSIMILAR MATERIAL BY ELECTRICAL RESISTANCE SPOT WELDING. - Mathi, K.; R.jinu, G. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Electrical resistance Spot Welding is a pressure welding used for joining of sheet metals or wires. The welding heat is produced at the desired location by electrical resistance through the metal pieces. ERSW is highly used due to its fast rate of production, less maintenance, free from smoke etc… ERSW is experimented in dissimilar materials (Stainless steel –Mild steel) to analyze the effect of process parameters such as welding current, welding time and electrode force. The welded parts were applicable to tensile test and hardness test .Thus the influence of parameters on weld quality was categorized.